Extracellular DNA as a Prognostic and Therapeutic Target in Mouse Colitis under DNase I Treatment - Bábíčková, J; Čonka, J; Janovičová, L; Boriš, M; Konečná, B; Gardlík, R (Folia biologica, 2018)
The aim of this study was to investigate the potential of extracellular DNA as a prognostic and/or therapeutic target in inflammatory bowel disease. Fifty male C57BL/6J mice were used in the experiment. Acute colitis was induced by intake of 2% dextran sulphate sodium (DSS) for seven days followed by three days of water intake. DNase I was injected intravenously on days 3 and 7. Plasmatic levels of extracellular DNA (ecDNA) were measured on days 6 and 10. Weight loss, stool consistency and liquid intake were monitored throughout the experiment. Colon length and weight, myeloperoxidase activity and tumour necrosis factor α (TNF-α) levels were measured at sacrifice. DSS-treated mice displayed severe colitis, as shown by disease activity parameters. Both groups with colitis (DNase treated and untreated) had significantly poorer weight loss, colon length and stool consistency compared with control groups on water. No differences between the DNasetreated and untreated DSS groups were recorded. Myeloperoxidase activity and levels of TNF-α in colonic tissue were notably greater in both groups with colitis compared to controls. In addition, both biochemical markers were improved in the DNasetreated group with colitis compared to the untreated group. Although the disease activity was proved by several independent parameters in both groups with colitis, levels of ecDNA did not show any difference between the groups throughout or at the end of experiment. The role of ecDNA in experimental colitis has not been confirmed. However, DNase I injection resulted in some improvement, and thus should be studied in more detail.
Keywords: Animals; biologické markery; Biomarkers; kolitida; DNA; cílená molekulární terapie; Mice; myši; prognóza; Deoxyribonuclease I; Male; Colitis; Prognosis; deoxyribonukleasa I; zvířata; mužské pohlaví; Mice, Inbred C57BL; Molecular Targeted Therapy; myši inbrední C57BL